2005
DOI: 10.1021/jm050333c
|View full text |Cite
|
Sign up to set email alerts
|

Carbonic Anhydrase Inhibitors:  Stacking with Phe131 Determines Active Site Binding Region of Inhibitors As Exemplified by the X-ray Crystal Structure of a Membrane-Impermeant Antitumor Sulfonamide Complexed with Isozyme II

Abstract: Structure for the adduct of carbonic anhydrase II with 1-N-(4-sulfamoylphenyl-ethyl)-2,4,6-trimethylpyridinium perchlorate, a membrane-impermeant antitumor sulfonamide, is reported. The phenylethyl moiety fills the active site, making van der Waals interactions with side chains of Gln192, Val121, Phe131, Leu198, Thr200. The 2,4,6-trimethylpyridinium functionality is at van der Waals distance from the aliphatic chain of Ile91 being involved in strong offset face-to-face stacking with Phe131. Analyzing X-ray cry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
115
0
1

Year Published

2008
2008
2009
2009

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 156 publications
(119 citation statements)
references
References 56 publications
3
115
0
1
Order By: Relevance
“…182 In addition to structural information, NMR also characterizes the internal motion of bound inhibitors [270][271][272][273][274] and of the enzyme active site itself. 272 Except for pentafluorobenzene-sulfonamide (212), which contains magnetically distinct environments for each fluorine atom when bound to HCA II, 271 the aromatic ring of benzenesulfonamides rotates rapidly on the NMR time scale about its C(1)-C(4) axis. 270,273,274 BCA II forms a 1:1 complex with p-methylbenzenesulfon-amide (6 , Table 10) at pH 6.0.…”
Section: Structures Determined By X-ray Crystallographymentioning
confidence: 99%
See 2 more Smart Citations
“…182 In addition to structural information, NMR also characterizes the internal motion of bound inhibitors [270][271][272][273][274] and of the enzyme active site itself. 272 Except for pentafluorobenzene-sulfonamide (212), which contains magnetically distinct environments for each fluorine atom when bound to HCA II, 271 the aromatic ring of benzenesulfonamides rotates rapidly on the NMR time scale about its C(1)-C(4) axis. 270,273,274 BCA II forms a 1:1 complex with p-methylbenzenesulfon-amide (6 , Table 10) at pH 6.0.…”
Section: Structures Determined By X-ray Crystallographymentioning
confidence: 99%
“…In a study relevant to the binding of arylsulfonamides to CA II, Krishnamurthy et al have recently reported the binding of fluorinated benzenesulfonamides (207)(208)(209)(210)(211)(212) to BCA II. 182 By constructing a quantitative structure-activity relationship (QSAR), the investigators separated the influence of fluorination of the ring on electrostatic-Lewis basicity of ArSO 2 NH − toward the Zn II cofactor and toward the hydrogen-bond network (interactions that they assumed were dependent on pK a )-and hydrophobic-contacts of the phenyl ring with the enzyme (an interaction that they assumed was dependent on log P, the logarithm of the octanol/aqueous buffer partition coefficient)-interactions (eq 22; Figure 16A).…”
Section: Brønsted Relationships Reveal the Role Of Basicity Of The Sumentioning
confidence: 99%
See 1 more Smart Citation
“…Compound 2 on the other hand, which is also a very strong CA IX inhibitor (K i of 14 nM) 125,295 , belongs to a class of positively charged, membrane-impermeant compounds previously reported by one of our groups 355 , which are highly attractive for targeting CA IX with its extracellular active site, since such compounds do not inhibit intracellular CAs, and may thus lead to drugs with fewer side effects as compared to the currently available compounds (acetazolamide is the prototypical one 293 ), which indiscriminately inhibit all CAs 293 . The X-ray crystal structure of compound 2 in adduct with CA II (whose active site is very similar to that of CA IX, as shown recently by homology modeling) has been reported recently 356 . It has been observed that the positively charged .…”
mentioning
confidence: 59%
“…It should be mentioned that since the X-ray structure of CA IX is not yet available, most studies used the CA II structure for modeling and designing CA IX inhibitors. We stress again that positively charged compounds, of which 2 is a representative, may have the advantage of selectively inhibiting only CA IX in vivo, due to their membrane impermeability 356 . Indisulam 3 is a sulfonamide derivative (originally called E7070) discovered through extensive screening/synthetic studies, which showed powerful anticancer activity in vitro and in vivo 349 .…”
mentioning
confidence: 92%